Role of Monocyte/Macrophages during HIV/SIV Infection in Adult and Pediatric Acquired Immune Deficiency Syndrome - Merino, Kristen M.; Allers, Carolina; Didier, Elizabeth S.; Kuroda, Marcelo J. (Frontiers in Immunology, 2017)
Monocytes/macrophages are a diverse group of cells that act as first responders in innate immunity and then as mediators for adaptive immunity to help clear infections. In performing these functions, however, the macrophage inflammatory responses can also contribute to pathogenesis. Various monocyte and tissue macrophage subsets have been associated with inflammatory disorders and tissue pathogeneses, such as occur during HIV infection. Nonhuman primate research of SIV has been invaluable in better understanding the pathogenesis of HIV infection. The question of HIV/SIV-infected macrophages serving as a viral reservoir has become significant for achieving a cure. In the rhesus macaque model, SIV-infected macrophages have been shown to promote pathogenesis in several tissues resulting in cardiovascular, metabolic and neurological diseases. Results from human studies illustrated that alveolar macrophages could be an important HIV reservoir and humanized myeloid-only mice supported productive HIV infection and viral persistence in macrophages during ART treatment. Depletion of CD4+ T cells is considered the primary cause for terminal progression, but it was reported that increasing monocyte turnover was a significantly better predictor in SIV-infected adult macaques. Notably, pediatric cases of HIV/SIV exhibit faster and more severe disease progression than adults, yet neonates have fewer target T cells and generally lack the hallmark CD4+ T cell depletion typical of adult infections. Current data show that the baseline blood monocyte turnover rate was significantly higher in neonatal macaques compared to adults and this remained high with disease progression. In this review, we discuss recent data exploring the contribution of monocytes and macrophages to HIV/SIV infection and progression. Furthermore we highlight the need to further investigate their role in pediatric cases of infection.